2023
DOI: 10.5851/kosfa.2023.e5
|View full text |Cite
|
Sign up to set email alerts
|

On-Farm and Processing Factors Affecting Rabbit Carcass and Meat Quality Attributes

Abstract: Ethics approval (IRB/IACUC) (This field may be published.) This article does not require IRB/IACUC approval because there are no human and animal participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 120 publications
0
0
0
Order By: Relevance
“…Since most of the chicken meat offered for commercial consumption in the market is hybrid, it is expected that the data obtained would be uniform. The moisture content found for rabbit meat in the study was similar to the moisture rates reported in other studies (Bhatt et al, 2023;Kumar et al, 2023). While the highest value in terms of ash ratio was determined for lamb (Figure 2); beef ash ratio was found to be lower than chicken meat (P<0.001).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Since most of the chicken meat offered for commercial consumption in the market is hybrid, it is expected that the data obtained would be uniform. The moisture content found for rabbit meat in the study was similar to the moisture rates reported in other studies (Bhatt et al, 2023;Kumar et al, 2023). While the highest value in terms of ash ratio was determined for lamb (Figure 2); beef ash ratio was found to be lower than chicken meat (P<0.001).…”
Section: Resultssupporting
confidence: 88%
“…The flavor of the meat consumed is related to softness, juiciness, aroma, and taste. A quality meat should be soft, high in moisture, containing more muscle fibers than connective tissue, pink in color, and have a suitable aroma (Kumar et al, 2023;Nutautaitė et al, 2023).…”
Section: Büşra Yaranoğlumentioning
confidence: 99%
See 1 more Smart Citation
“…[178], [179], [180], [181] Rabbit meat Biological activity; factors affecting quality; meat quality; quality determinants; rabbit breeds [182] Satellite cell Adipogenesis; AKT/AMPK signaling pathway; antimicrobial peptide; apolipoprotein H; blood removal; C2C12 myoblast cell; carcass chilling method; cell growth; chicken; CopA3; culture temperature; cultured meat; differentiation; fat; food safety; genetic analysis; growth factors; Hanwoo; myosatellite cell; hormone-lipid metabolism; meat color; meat quality; muscle satellite [30], [183], [184], [185], [186],…”
Section: Discussionmentioning
confidence: 99%
“…Different rabbit breeds and the anatomical location of muscles may also affect the nutritional profile and physicochemical properties of rabbit meat (Kumar et al, 2023) The main components determining the economic efficiency of rabbit breeding with the full realization of the genetic potential of animals and a good feed base are their productive, maternal, reproductive, and technological characteristics, which are necessary components of breeding work aimed at the improvement of parental forms. To stabilize and increase this indicator, it is necessary to establish a set of measures to improve the maintenance, as well as to carry out constant control of the veterinary support of the industry and conduct selective and breeding work with the rabbit breeding herd (Luchyn, 2022;Bolet et al, 2000;Lesyk et al, 2021).…”
Section: Introductionmentioning
confidence: 99%